HLA Alleles B*53:01 and C*06:02 Are Associated With Higher Risk of P. falciparum Parasitemia in a Cohort in Uganda - Digitale, Jean C.; Callaway, Perri C.; Martin, Maureen; Nelson, George; Viard, Mathias; Rek, John; Arinaitwe, Emmanuel; Dorsey, Grant; Kamya, Moses; Carrington, Mary; Rodriguez-Barraquer, Isabel; Feeney, Margaret E. (Frontiers in Immunology, 2021)
Variation within the HLA locus been shown to play an important role in the susceptibility to and outcomes of numerous infections, but its influence on immunity to P. falciparum malaria is unclear. Increasing evidence indicates that acquired immunity to P. falciparum is mediated in part by the cellular immune response, including NK cells, CD4 and CD8 T cells, and semi-invariant  T cells. HLA molecules expressed by these lymphocytes influence the epitopes recognized by P. falciparum-specific T cells, and class I HLA molecules also serve as ligands for inhibitory receptors including KIR. Here we assessed the relationship of HLA class I and II alleles to the risk of P. falciparum infection and symptomatic malaria in a cohort of 892 Ugandan children and adults followed prospectively via both active and passive surveillance. We identified two HLA class I alleles, HLA-B*53:01 and HLA-C*06:02, that were associated with a higher prevalence of P. falciparum infection. Notably, no class I or II HLA alleles were found to be associated with protection from P. falciparum parasitemia or symptomatic malaria. These findings suggest that class I HLA plays a role in the ability to restrict parasitemia, supporting an essential role for the cellular immune response in P. falciparum immunity. Our findings underscore the need for better tools to enable mechanistic studies of the T cell response to P. falciparum at the epitope level and suggest that further study of the role of HLA in regulating pre-erythrocytic stages of the P. falciparum life cycle is warranted.